1999
DOI: 10.1051/aas:1999113
|View full text |Cite
|
Sign up to set email alerts
|

The stark broadening effect in hot star atmospheres: Au I and Au II lines

Abstract: Abstract. The Stark broadening parameters for six Au I lines and eight Au II transitions have been calculated. Two methods for calculation have been used: the semiclassical method (for Au I lines) and the modified semiempirical approach (for Au II transitions). In the case of Au II, the jj coupling approximation has been used for the matrix-element calculations. The importance of the electron-impact effect in the case of Au II λ = 174.0476 nm line for several stellar atmosphere models has been tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 18 publications
(27 reference statements)
0
28
0
Order By: Relevance
“…Spectral lines of highly charged chromium ions, including Cr VI, have been observed in the spectra of white dwarf atmospheres where, as it has been demonstrated several times [12,13,14,15,16,17,18,19,20,21,10], Stark broadening is usually dominant line broadening mechanism. With the results obtained here, we also wish to demonstrate the importance of Stark broadening in DO white dwarf atmospheres, which effective temperature is within the range 40 000 K < T ef f < 120 000 K.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral lines of highly charged chromium ions, including Cr VI, have been observed in the spectra of white dwarf atmospheres where, as it has been demonstrated several times [12,13,14,15,16,17,18,19,20,21,10], Stark broadening is usually dominant line broadening mechanism. With the results obtained here, we also wish to demonstrate the importance of Stark broadening in DO white dwarf atmospheres, which effective temperature is within the range 40 000 K < T ef f < 120 000 K.…”
Section: Resultsmentioning
confidence: 99%
“…For example, at temperatures around 10 4 K and densities 10 13 -10 15 cm −3 , Stark broadening is of interest for modelling and analysing spectra of A and B type stars (see e.g. Lanz et al (1988); Popović et al (1999a); Popović et al (1999b); Popović et al (2001a,b); Tankosić, Popović & Dimitrijević (2003); Simić et al (2005a,b)). In white dwarfs, especially Stark broadening is the dominant collisional line broadening mechanism in all important layers of the atmosphere (Popović et al 1999b;Tankosić, Popović & Dimitrijević 2003;Milovanović et al 2004;Simić et al 2006;Dimitrijević et al 2011;Dufour et al 2011;Larbi-Terzi et al 2012;Simić, Dimitrijević & Sahal-Bréchot 2013;Simić, Dimitrijević & Popović 2014).…”
Section: The Impact Semiclassical Perturbation Methodsmentioning
confidence: 99%
“…This broadening mechanism may be of interest and for the main sequence stars, especialy for A type and late B type (Lanz et al 1988;Popović et al 1999a;Popović et al 1999b;Popović et al 2001a,b;Dimitrijević et al 2003a,b;Tankosić, Popović & Dimitrijević 2003;Dimitrijević et al 2004;Milovanović et al 2004;Dimitrijević et al 2005;Simić et al 2005a,b;Simić, Dimitrijević & Kovačević 2009;Simić, Dimitrijević & Sahal-Bréchot 2013;Simić, Dimitrijević & Popović 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium in various ionization stages from Cr I to Cr VI has been observed and in the spectra of white dwarfs, where the Stark broadening is often the dominant broadening mechanism in wide layers of the atmosphere [19][20][21][22][23][24][25][26][27]. For example, Cr I has been found by Gianninas et al [28] in an extremely low mass white dwarf in the SDSS J074511.56+194926.5 binary system and by Dufour et al [29] in the spectrum of DZ white dwarf G165-7; Cr II spectral lines were identified by Klein et al [30] in the spectrum of white dwarf GD 40, observed on the Keck I telescope at Mauna Kea Observatory; and, for example, Cr V and Cr VI by Rauch et al [31] in the spectrum of the white dwarf central star of Sh 2-216.…”
Section: Introductionmentioning
confidence: 99%